If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m + n) + (5m + -2) = 0 Remove parenthesis around (m + n) m + n + (5m + -2) = 0 Reorder the terms: m + n + (-2 + 5m) = 0 Remove parenthesis around (-2 + 5m) m + n + -2 + 5m = 0 Reorder the terms: -2 + m + 5m + n = 0 Combine like terms: m + 5m = 6m -2 + 6m + n = 0 Solving -2 + 6m + n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 6m + 2 + n = 0 + 2 Reorder the terms: -2 + 2 + 6m + n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 6m + n = 0 + 2 6m + n = 0 + 2 Combine like terms: 0 + 2 = 2 6m + n = 2 Add '-1n' to each side of the equation. 6m + n + -1n = 2 + -1n Combine like terms: n + -1n = 0 6m + 0 = 2 + -1n 6m = 2 + -1n Divide each side by '6'. m = 0.3333333333 + -0.1666666667n Simplifying m = 0.3333333333 + -0.1666666667n
| 4x^2+26x+53=0 | | X-1=6.59 | | h=-16t^2+149t+98 | | 2/x-3/2x=1/3 | | 3^-2(x^2)/x^3(y^-1) | | 42x+2=0 | | 13(3x-2)=7(6x-5) | | 4(5x+15)=20(4x-36) | | 2(3x-3.3)=4x-6.6 | | 2/a-1/b | | -0.7x+6.31=-0.5x+1.31 | | 2.4x-69=1.2x+9 | | (3x^2-16x+21)=0 | | -12/x^2/19/3x | | 171/3 | | 2(x-2.8)=8.8 | | (2x^2-7x+3)=0 | | 3(x-2)=10+x | | (3x+5)(2x^2-7x+3)=0 | | 194xy,1/2x,z | | n^2+10n-80=0 | | 5x^3y^6z^2+15xy^3z^3-25x^6y^2z^3= | | 10x^2+5x-225=0 | | 12/17x=21/34 | | 3x^3+22x^2-80x=0 | | 15-1/3x=8 | | 6x-7=5x+14 | | 3x(y-13)=5xy(2) | | 324+3x=609 | | 7r^2+5r^2-10r^2= | | 5x+12=6x-17 | | 10y=10+20x |